MicroRNA-33b Suppresses Epithelial–Mesenchymal Transition Repressing the MYC–EZH2 Pathway in HER2+ Breast Carcinoma - Pattanayak, Birlipta; Garrido-Cano, Iris; Adam-Artigues, Anna; Tormo, Eduardo; Pineda, Begoña; Cabello, Paula; Alonso, Elisa; Bermejo, Begoña; Hernando, Cristina; Martínez, María Teresa; Rovira, Ana; Albanell, Joan; et al. (Frontiers in Oncology, 2020)
Downregulation of miR-33b has been documented in many types of cancers being involved in proliferation, migration and epithelial-mesenchymal transition (EMT). Further, EZH2 is a master regulator controlling stem cell differentiation and cell proliferation processes. We aim to evaluate the implication of miR-33b in the EMT pathway in HER2+ breast cancer and to analyze the role of EZH2 in this process as well as the interaction between them. MiR-33b is downregulated in HER2+ breast cancer cells vs healthy controls and negatively correlated with EZH2 in vivo and in vitro. Upregulation of miR-33b suppressed proliferation, induced apoptosis, reduced invasion and migration and regulated EMT by an increase of E-cadherin, and a decrease of ß-catenin and vimentin. The silencing of EZH2 mimicked the impact of miR-33b overexpression. Furthermore, the inhibition of miR-33b induces cell proliferation, invasion, migration, EMT and EZH2 expression in non-tumorigenic cells. Importantly, the Kaplan-Meier analysis showed a significant association between high miR-33b and better overall survival. These results suggest miR-33b as a suppressive miRNA that could inhibit tumour metastasis and invasion in HER2+ BC partly by impeding EMT through repression of the MYC-EZH2 loop.